2019
DOI: 10.1039/c8ra09879d
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced thermal conductance at the graphene–water interface based on functionalized alkane chains

Abstract: This work demonstrates an effective and universal method to improve thermal transport properties on the interface between multilayer graphene and water by a factor of ~4 via grafting functionalized groups on graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Heat carriers of high frequency are important to thermal transport across interfaces [ 28 , 30 , 31 ]. As previously described, the oxidation of graphene (GO and rGO) provided phonon vibrations at high frequencies that are not present in the pristine graphene (G).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat carriers of high frequency are important to thermal transport across interfaces [ 28 , 30 , 31 ]. As previously described, the oxidation of graphene (GO and rGO) provided phonon vibrations at high frequencies that are not present in the pristine graphene (G).…”
Section: Resultsmentioning
confidence: 99%
“…The phonons play an important role in the thermal conductivity across the interface between two phases or materials, so the study of this type of vibration mode gives a deep understanding of the influence of atomistic properties on a property such as this [ 26 , 27 ]. The DOS was computed by calculating the Fourier transformation of the atomic velocity autocorrelation functions [ 28 ]: where v (0) and v ( t ) are the velocities of each atom at initial time and time t , respectively, and ω is the frequency. The DOS spectra of graphene fillers and polymers were obtained by monitoring the velocity autocorrelation function of the corresponding atoms.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, when there is both a substrate and a medium on top, the propagation of heat in graphene is distinguished from the suspension graphene. [29][30][31][32] Contact with a substrate and a medium on top could results in a decrease in the thermal conductivity of graphene.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was shown that the local thermal conductivity of the aqueous shell adjacent to the nanoparticle is approximately 50% higher than in volumetric water [ 57 ]. The calculations were made for metal particles [ 56 , 57 ] and systems containing graphene (4∙10 −8 m 2 K W −1 ) [ 55 , 58 ] and carbon nanotubes [ 59 ].…”
Section: Discussionmentioning
confidence: 99%